PENERAPAN METODE PEMETAAN PIKIRAN DENGAN MEDIA AUDIOVISUAL UNTUK MENINGKATKAN KEMAMPUAN MENULIS PUISI SISWA - Wahyuni, Dwita; Sulissusiawan, Ahadi; Salem, Laurensius (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe research was based on the lack of studentsâ€™ writing skill. The evidence was seen from the students writing achievement which were mostly below Minimum Passing Grade scor, 72,22. In the poetry writting learning, the students were less skilled in writing their ideas to poetry. This research is focused on poetry writting learning by using mind mapping method with audiovisual media. Problem in this research is â€œhow is the use, evaluation to see the achievement, and learning constraints by using mind mapping method with audiovisual media?â€ This research aims to investigate the use, evaluation to see the achievement, and learning constraints by using mind mapping method with audiovisual to enhance poetry writing ability. Method used was descriptive with Classroom Action Research (CAR) model. Technique used was indirect technique namely observation and documentary study. Tools of collecting data were observation guide namely IPKKG 1 and IPKG 2, and studentâ€™s scoring sheet. Analysis technique used was qualitative descriptive. The results, showed average score in pre-cycle was 54,26, while the average score in the first cycleÂ was 73,12, and the average score in the second cycleÂ was 87,70. Thus, the poetry writing ability by using mind mapping method with audiovisual media is increased from the pre-cycle, the first cycle, and the second cycle.Â Â Â Â Â Â Â Â Â . Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Keywords: Mind Mapping, Audiovisual, Poetry, Writing AbilityÂ